2004
DOI: 10.1002/adv.20012
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electrical conductivity in poly(maleic anhydride‐alt‐acrylic acid) and its transition metal complexes

Abstract: Poly(maleic anhydride-alt-acrylic acid) and its transition-metal complexes with Ni(II), Cu(II), and Cd(II) were synthesized. Poly(maleic anhydride-alt-acrylic acid) was characterized using Fourier transform infrared (FTIR), titration, viscometry, differential scanning calorimetry (DSC), and POLY(MALEIC ANHYDRIDE-alt-ACRYLIC ACID) AND ITS TRANSITION METAL COMPLEXESthermogravimetric (TGA) analysis. The temperature dependence of the conductivity of the copolymer and polychelates of transition metals was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…In recent years, a special attention has been focused to explore the possibility of using polymer materials with their transition metal complexes as potent biomaterials and thermally stable materials due to their capability of exhibiting novel and unusual properties . Consequently, many polymers are now being synthesized, tested, and used not only for their macromolecular properties (the bulk properties of the polymers) but also for the properties of their chosen aromatic and aliphatic monomers with the functional groups containing nitrogen, sulfur, and oxygen (N, S, and O) donor atoms .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a special attention has been focused to explore the possibility of using polymer materials with their transition metal complexes as potent biomaterials and thermally stable materials due to their capability of exhibiting novel and unusual properties . Consequently, many polymers are now being synthesized, tested, and used not only for their macromolecular properties (the bulk properties of the polymers) but also for the properties of their chosen aromatic and aliphatic monomers with the functional groups containing nitrogen, sulfur, and oxygen (N, S, and O) donor atoms .…”
Section: Introductionmentioning
confidence: 99%
“…Some specific research has shown the usefulness of polychelates include complexes between poly (acrylic acid) and divalent, trivalent, and tetravalent metal ions and the stability constants for complex‐formation determined 20–22. The crystalline behavior and temperature‐dependent electrical conductivity23 of the Cu, Ni, and Cd polychelates formed with poly(maleic acid‐ alt ‐acrylic acid) at different pH values were determined by X‐ray diffraction spectroscopy 17, 24. Other polychelates have been prepared and studied including a terpolymer of ethyl methacrylate, N ‐phenylmaleimide, and itaconic acid, poly (EMA‐ co ‐PhMI‐ co ‐IA) complexed with Cu 2+ , Co 2+ , and Ni 2+ ions 25.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallinity degrees and temperature-dependent electrical conductivities of poly(MA-alt-AA)-Cu(II), poly(MA-alt-AA)-Ni(II), and poly(MA-alt-AA)-Cd(II) complexes were investigated by the X-ray powder diffraction method 16 and electrical conductivity measurements. 17 The aim of this work was to investigate the metal complexation and thermal stability of poly(MA-alt-AA) in the presence of copper(II), nickel(II), and cadmium(II) chlorides. At a distinct pH, the influence of these metal ions on the formation of the complexation was studied with gravimetric analysis and thermal analysis measurements.…”
Section: Introductionmentioning
confidence: 99%